Analisis Pertumbuhan Fase Superkonduktor BSCCO-2212 dan BPSCCO-2212 Akibat Variasi Suhu Sintering Menggunakan Metode Pencampuran Basah - Karo, Pulung Karo; Ramadhan, Risky Putra; Suprihatin, Suprihatin; Yulianti, Yanti (Journal of Energy, Material, and Instrumentation Technology, 2021)
The research was conducted to determine the effect of sintering temperature on the level of purity of the superconducting phase BSCCO-2212 and BPSCCO-2212 using the wet mixing method. Sintering was carried out for 20 hours with variations in sintering temperature: 825, 830, 835 and 840°C. XRD results showed that the phase purity level increased until it reached the optimum point at 835°C sintering temperature and then decreased at 840°C. The highest volume fraction of the BSCCO-2212 sample was obtained at a sintering temperature of 835°C at 71.09% and the highest degree of orientation was obtained at a sintering temperature of 830°C at 26.44%. In the BPSCCO-2212 sample, the highest volume fraction was obtained at a sintering temperature of 835°C at 52.59% and the highest degree of orientation at a sintering temperature of 830°C at 43.49%. The results of the comparison of BSCCO-2212 and BPSCCO-2212 samples showed that the BPSCCO-2212 sample had a higher level of phase purity than BSCCO-2212.